GENETIC PERSISTENCY ON MILK PRODUCTION IN LOCAL AND TURKISH AWASSI SHEEP - AL-Samrai, Wafaa I.; AL-Gelawy, Jafar R.; Elia, Jayel V.; AL-Jawbai, Hmoud M. (Diyala Agricultural Sciences Journal, 2010)
Statistical analysis was used on 500 milk production records of Awassi sheep at the Sheep and Goat Research Station, State Board for Agricultural Research, the analysis was containing (134 Iraqi Awassi) and (366 Turkish Awassi ) on period of 2008 – 2009. The aim of this investigate the estimation of genetic persistency on milk production from the difference between genetic estimation to produce 120 days from genetic estimation to produce first 60 days of milk season in Local & Turkish Awassi sheep after studying the effect of fixed factors and estimation heritability to produce 60 and 120 milk day. The over all mean of milk production at the first 60 days and 120 days of milk season was 54.92 and 107.56 kg respectively. Research result shows that all of studied fixed factors ( breed ، dam age at calving ، calving season and kind of calving ) were significant effect on milk production in 60 and 120 days. The heritability of milk production at 60 and 120 days was 0.28 and 0.24 respectively. There was a large variation in genetic values estimation of rams used in this research at 60 and 120 days. On the other hand the maximum estimation of genetic persistency was 8.26 kg , while the minimum was 6.50 kg ، and depending of those estimations will affair on increasing genetic gain and economically later in the flock.